Organic livestock husbandry: An approach to welfare & sustainability (Indian Journal of Animal Production and Management, 2017)
Organic term primarily and simply reflects  something very close to nature, ethics and  tradition in general and involves principles that  generate products of high quality, coherent with  environment in particular23. According to the Codex  Alimentarius Commission and all existing national  regulations, “organic production is a holistic  production management system that avoids use  of synthetic fertilizers, pesticides and genetically  modified organisms, minimizes pollution of air, soil  and water, and optimizes the health and productivity  of interdependent communities of plants, animals  and people”. Organic farming is being promoted as  an ideal practice in addressing the environmental  protection, food safety and sustainability concerns.  The thought of organic farming is to establish and  maintain soil–plant, plant–animal and animal–soil  interdependence and to create a sustainable agro  ecological system based on local resources. The  most important characteristic of organic farming is  the emphasis on the production process rather than  the product itself.